EVALUASI PROSES PEMBANGUNAN SARANA DAN PRASARANA PENDIDIKAN DI KECAMATAN TEBING TINGGI TIMUR PASCA LIMA TAHUN PEMEKARAN KABUPATEN KEPULAUAN MERANTI - Rastra, Tio; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Education is one form of investment to human resources will be an asset in the development of the nation in the future. Therefore, people must receive affordable and quality education, through quality education and low through 9-year compulsory education program. An attempt by the government and society Regency Meranti to develop human resources which has the quality of academic competence high, intelligent, moral, faithful, devoted, responsive environments and has the ability (hard and soft skills) is high, so that they can live and compete in employment free.This study aimed to evaluate the development process of educational facilities in the district of East Cliff High after five years of expansion Meranti Islands District. Policy theory and the theory of evaluation is a cornerstone in this study. This study uses qualitative research. Based on the analysis that has been done, the process of construction of educational facilities in the district of East High Cliff is still not in accordance with national education standards as referring to the existing regulations. But the government's efforts in meeting the standardization it is still running today. And the development of educational infrastructure is still running despite the lack of constrained budget allocation.Keywords: Policy, Evaluation and Education Facilities and Infrastructure